2012
DOI: 10.1017/s0950268812002701
|View full text |Cite
|
Sign up to set email alerts
|

Impact of neonatal hepatitis B vaccination programme on age-specific prevalence of hepatitis B infection in teenage mothers in Hong Kong

Abstract: We examined the impact of the neonatal hepatitis B immunization programme, first provided to all neonates born to mothers screened positive for hepatitis B surface antigen (HBsAg) in late 1983, on the age-specific prevalence of HBsAg carriage in teenage mothers managed in 1998–2008. HBsAg carriage was found in 2.5%, 2.7%, 8.8% and 8.0% of mothers aged ≤ 16, 17, 18, and 19 years, respectively (P=0.004), which was also correlated with advancing age (P=0.011). While neither difference nor correlation with age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…A recent study in the UK showed that 84.6% of children immunized with three doses of the vaccine at infancy have persistent immunity,14 while our study found that 67.9% (171/252) of subjects who received three doses had persisting protective anti-HBs, with significant association to the number of doses ( P < 0.05). Our results also revealed declining anti-HBs titers within a year of vaccination, similar to findings in previous related studies1517 and in concurrence with findings in Brazil, which reported a positive correlation between anti-HBs titers after primary vaccination with the duration of the vaccination 18. Persistence of antibody has long been considered a marker for vaccine protection; nevertheless, a better understanding of immunology has led to the understanding that long-term protection is also conferred by immune memory cells.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study in the UK showed that 84.6% of children immunized with three doses of the vaccine at infancy have persistent immunity,14 while our study found that 67.9% (171/252) of subjects who received three doses had persisting protective anti-HBs, with significant association to the number of doses ( P < 0.05). Our results also revealed declining anti-HBs titers within a year of vaccination, similar to findings in previous related studies1517 and in concurrence with findings in Brazil, which reported a positive correlation between anti-HBs titers after primary vaccination with the duration of the vaccination 18. Persistence of antibody has long been considered a marker for vaccine protection; nevertheless, a better understanding of immunology has led to the understanding that long-term protection is also conferred by immune memory cells.…”
Section: Discussionsupporting
confidence: 92%
“…We observed recently that the prevalence of HBV infection in university students in Hong Kong SAR, increased with age: it was 0.9%, 2.3%, 4.3% and 5.5% in those aged ≤ 18, 19, 20 and ≥ 21 years, respectively 30 . The prevalence also increased with age among women who underwent antenatal screening at our hospital: it was 2.5%, 2.7%, 8.8% and 8.0% in those aged ≤ 16, 17, 18 and 19 years, respectively 31 . These findings suggest that immunity against HBV infection wanes in late adolescence, which could explain the persistently high prevalence of HBsAg carriage we observed in pregnant women.…”
Section: Introductionmentioning
confidence: 63%
“…This is important in Asia where eating and living with in-laws after marriage is common. It could be that exposure of individuals with declining immunity to infection was one reason for the increase in the prevalence of HBsAg carriage from 1.9% in adolescents to 4.9% in those aged 20 to 30 years reported in the Republic of Korea 43 and for our earlier observation that the prevalence of HBV infection rose rapidly among teenagers in Hong Kong SAR 30 , 31 …”
Section: Discussionmentioning
confidence: 90%
“…However, when teenage mothers in Hong Kong were studied, the prevalence of HBV infection increased significantly from 1.2%, 1.5%, CONTACT Terence T. Lao lao-tt@cuhk.edu.hk 7.1% to 8.3% for those at age 16, 17, 18, and 19 years respectively, and which was correlated with (P D 0.002) age. 24 Indeed, among young mothers born in Hong Kong who should have been protected by hepatitis B vaccination administered in infancy, HBV infection increased from 2.3% at age 16 years to peak at 8.4% at age 25 years. 25 In fact, by age 18 years, the 6.9% prevalence of HBV infection in the parturients born in/ after 1984, when all high risk newborn infants would have been protected by HBV immunization, was comparable to the figure in 1976, 20 while the prevalence of 8.0% in those aged 22 years even exceeded the figure in 1981-1983.…”
Section: Prevalence Of Hbv Infection In Hong Kongmentioning
confidence: 99%
“…For the occurrence of specific vaccine-preventable disease such as HBV infection in pregnant women born after the introduction of neonatal vaccination, this would be compatible with the category of confirmed clinical vaccine failure. 32 Nevertheless, as the aforementioned studies conducted in the pregnant women in Hong Kong 22,24,25 were retrospective in design, there was no means of confirmation or documentation of vaccination history. Yet there is evidence that the hepatitis B vaccine may not provide such long term protection as widely held.…”
Section: Is There Evidence Of Hbv Vaccine Failure?mentioning
confidence: 99%